Pedestrian satisfaction assessment framework on urban facilities accessibility of commercial neighbourhood zones - Anjomshoaa, Elahe (2017)
In recent times urban designers, planners, landscape architects, and architects are emphasising the studies of pedestrian behaviour, accessibility and satisfaction. Although the concept of users’ satisfaction has gained considerable attention in the field of urban design; few studies have focused on the assessment of pedestrian satisfaction. Thus, this research aims to develop a Pedestrian Satisfaction Assessment Framework (PSAF) to evaluate pedestrian satisfaction, attitude, and preference with regard to accessibility to the neighbourhood facilities in commercial zones. This study’s framework establishes the relationships between pedestrian behaviour and accessibility towards urban design strategies that can improve pedestrian satisfaction. The various aspects of pedestrian satisfaction, and the diverse urban accessibility features are relevant to be adopted in diverse design approaches that will produce more satisfactory pedestrian environments. For this study, the urban facilities and its subitems in commercial zones were identified in order to measure pedestrian satisfaction. Therefore, Kano satisfaction assessment model was adopted accordingly, while the Pedestrian Satisfaction Assessment Framework (PSAF) for evaluation of urban facilities accessibility in commercial zones was developed and validated through a pilot study within some selected commercial neighbourhoods. For the purpose of this study, accessibility with a 500 meter walking radius of pedestrians for three commercial neighbourhood zones within Johor Bahru city were considered. The three zones are: Taman Universiti, Taman Tun Aminah, and Taman Pulai Utama. Respondents residing in the three neighbourhoods for more than eight years and have walking access to commercial zones were the subject target. Data from respondents via questionnaires was analysed by Kano model equation and SPSS. The analysed data showcased the present and future framework requirements that can be used by urban designers, urban planners, landscape architects, and architects for future sustainable urban development of commercial zones. The final framework is recommended as a design decision supporting tool for urban professionals to make more accurate decisions on urban development or redevelopment.